Poly(propylene carbonate) networks with excellent properties: Terpolymerization of carbon dioxide, propylene oxide, and 4,4ʹ-(hexafluoroisopropylidene) diphthalic anhydride - Zhang Yi-Le (De Gruyter, 2021)
Poly(propylene carbonate) (PPC) is an emerging low-cost biodegradable plastic with potential application in many fields. However, compared with polyolefin plastics, the major limitations of PPC are its poor mechanical and thermal properties. Herein, a thermoplastic PPC containing cross-linked networks, one-pot synthesized by the copolymerization of carbon dioxide, propylene oxide, and 4,4ʹ-(hexafluoroisopropylidene) diphthalic anhydride, had excellent thermal and mechanical properties and dimensional stability. The weight-average molecular weight and the polymer yield of the PPC5 were up to 212 kg mol−1 and 104 gpolym gcat −1, respectively. The 5% thermal weight loss temperature reached 320°C, and it could withstand a tensile force of 52 MPa. This cross-linked PPC has excellent properties and is expected to be used under extreme conditions, as the material can withstand strong tension and will not deform.